Monitoring the agri-food system in Myanmar: Rice millers – November 2021 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
Rice mills are the primary link in the rice value chain between farmers and consumers. Therefore, it is critical to monitor milling shocks as they will affect both farmers' incomes and urban rice prices. Since June 2020, we have monitored the impact of COVID-19 and political instability on rice millers in Myanmar and this is the tenth Research Note in the series. In this Research Note, we present evidence from interviews with 392 rice millers conducted in November 2021 in Myanmar’s three major rice-growing regions–Ayeyarwady, Bago, and Yangon. We present evidence of the current situation in relation to previous survey rounds, including 1) disruptions in milling caused by the political and health crises; 2) changes in operations such as throughput, paddy and rice storage, and working capital; 3) reasons for expected throughput changes in the 2021 monsoon harvest season; and 4) prices of paddy, rice, and byproducts.